2016
DOI: 10.1002/mnfr.201600037
|View full text |Cite
|
Sign up to set email alerts
|

Gartanin, an isoprenylated xanthone from the mangosteen fruit (Garcinia mangostana), is an androgen receptor degradation enhancer

Abstract: Gartanin is an isoprenylated xanthone that promotes AR degradation with evidence suggesting this process is critically regulated by the unfolded protein response pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 34 publications
1
22
0
1
Order By: Relevance
“…The ERS response pathway is key in protein quality control through the UPR and downstream autophagy activation (Figure S1) . Previous studies have shown that riluzole induces ER morphological distress in PCa cells and ERS is involved in AR protein degradation . Indeed, our data show that thapsigargin, a potent ERS inducer, decreased expression of AR and AR target genes (Figures E and 1F).…”
Section: Resultssupporting
confidence: 55%
See 3 more Smart Citations
“…The ERS response pathway is key in protein quality control through the UPR and downstream autophagy activation (Figure S1) . Previous studies have shown that riluzole induces ER morphological distress in PCa cells and ERS is involved in AR protein degradation . Indeed, our data show that thapsigargin, a potent ERS inducer, decreased expression of AR and AR target genes (Figures E and 1F).…”
Section: Resultssupporting
confidence: 55%
“…21 Previous studies have shown that riluzole induces ER morphological distress in PCa cells and ERS is involved in AR protein degradation. [17][18][19]26 Indeed, our data show that thapsigargin, a potent ERS inducer, decreased expression of AR and AR target genes ( Figures 1E and 1F). Since reduction of AR target gene expression by thapsigargin was analogous to riluzole's effect, we hypothesized that riluzole may induce ERS.…”
Section: Rna Extraction Cdna Synthesis and Quantitative Real-timementioning
confidence: 65%
See 2 more Smart Citations
“…Several studies revealed the anticancer activities of xanthones derivative from GM [35][36][37][38][39][40][41]. In HL60 cell line, six xanthones (α-, β-, γ-mangostin, mangostinone, garcinone E and 2-isoprenyl-1, 7-dihydroxy-3-methoxy xanthone) possessed the cytotoxic effect by inhibiting cell growth, while the α-mangostin exerted the highest inhibitory activity than others [3].…”
Section: Anti-tumoral Propertiesmentioning
confidence: 99%